Where Are Migrants from? Inter- vs. Intra-Provincial Rural-Urban Migration in China - Yaqin Su; Petros Tesfazion; Zhong Zhao (Global Labor Organization (GLO), 2017)
Using a representative sample of rural migrants in cities, this paper investigates where the migrants in urban China come from, paying close attention to intra-provincial vs. inter-provincial migrants, and examining the differences in their personal attributes. We find that migrants who have come within the province differ significantly from those who have come from outside of the province. Using a nested logit model, we find that overall, higher wage differentials, larger population size, higher GDP per capita, and faster employment growth rate are the attributes of a city that attract migrants from both within and outside province. In addition, moving beyond one's home province has a strong deterrent effect on migration, analogous to the “border effect” identified in international migration studies. We also explore the role of culture, institutional barrier, and dialect in explaining such a pronounced “border effect”.
Keywords: J62; O15; 330; Rural-urban migration; Inter- vs. intra-provincial migration; Border effect; China